2020
DOI: 10.1103/physrevapplied.14.014015
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hidden Gratings through Multilayer Nanostructures Using Light and Sound

Abstract: We report on the detection of diffraction gratings buried below a stack of tens of 18-nm-thick SiO 2 and Si 3 N 4 layers and an optically opaque metal layer, using laser-induced, extremely high-frequency ultrasound. In our experiments, the shape and amplitude of a buried metal grating are encoded on the spatial phase of the reflected acoustic wave. This grating-shaped acoustic reflection of the buried grating is detected by the diffraction of a delayed probe pulse. A detailed understanding of our measurements … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Due to these high-frequency acoustic waves, we measure oscillatory changes of the reflection on the order of 1%. Analysis of these oscillations and their respective frequencies suggest that we observe multiple types of acoustic waves, three of which we identify as longitudinal waves (LWs) [3,27,28], surface waves [3,[48][49][50][51], and grating line quasi-NM oscillations [50,52,53]. We find that the phase of the LWs and the grating line NMs experiences a π phase shift when the wavelength is tuned around the SPP resonance wavelength.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Due to these high-frequency acoustic waves, we measure oscillatory changes of the reflection on the order of 1%. Analysis of these oscillations and their respective frequencies suggest that we observe multiple types of acoustic waves, three of which we identify as longitudinal waves (LWs) [3,27,28], surface waves [3,[48][49][50][51], and grating line quasi-NM oscillations [50,52,53]. We find that the phase of the LWs and the grating line NMs experiences a π phase shift when the wavelength is tuned around the SPP resonance wavelength.…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, these photoacoustic waves have been used to study a variety of material properties and physical phenomena, such as thermal and electron diffusion [7][8][9][10], electron-hole plasmas in semiconductors [11], hot-electron-induced pressure [12,13], elastic constants of single layer [14][15][16][17] and multilayer structures [18,19], the electronic structure of materials [20,21], surface deformation dynamics [22][23][24][25], and the generation of terahertz radiation [26]. Furthermore, laser-induced acoustic echoes have been used for the detection of buried gratings [27,28], showing promise for applications in the semiconductor device manufacturing industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that laser-induced ultrasound can be employed for the detection of micro-and nano-structures buried underneath metal layers [31]. With this technique, we were able to detect gratings underneath optically opaque layers and dielectric multilayers, even after propagation of the acoustic wave through as many as 2 × 20 dielectric layers.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] can be used to detect gratings buried below optically opaque layers. 19,20 In this technique, diffraction off an acoustic replica of the buried grating is used to detect the presence of the optically hidden grating. In this way, we were able to detect buried gratings even after propagation of the acoustic wave through as many as 2 Â 20 dielectric layers.…”
mentioning
confidence: 99%